Can Antimicrobial Photodynamic Therapy (aPDT) Enhance the Endodontic Treatment? - Chiniforush, Nasim (J Lasers Med Sci, 2016)
In order to achieve a long-lasting effect, one of the main goals in root canal treatment is to eliminate the endodontic bacteria. Conventional chemomechanical debridement is considered as the basic treatment in root canal therapy, but adjunctive techniques such as antimicrobial photodynamic therapy (aPDT) can also be helpful. The aim of this study was to evaluate reports in the scientific literature that used different photosensitizers (PSs) for bacterial reduction. The literature search was conducted using databases including PubMed, Scopus, and Google Scholar with the keywords "photodynamic therapy," "antimicrobial photodynamic therapy," or "photoactivated disinfection" and "endodontic," "Enterococcus faecalis," or "root canal treatment," from 2000 to 2015. By evaluating different studies, it was concluded that aPDT should be applied in combination with conventional mechanical debridement and irrigants. However, it is also important to note that the success rate is critically dependent on the type of the PS, output power of the laser used, irradiation time, pre-irradiation time, and type of tips used.